Examining the Relationship Between Quality of Golfing Facility and User Experience on Customer Satisfaction and Revisit Intention in Jabodetabek, Indonesia - Yanto Ramli; Sri Hartono; Agustinus Hariadi Djoko Purwanto; Adi Nurmahdi (Journal of Consumer Sciences, 2026)
Background: Golf in urban regions such as Jabodetabek, Indonesia, is gaining wider appeal. Today’s players are increasingly influenced by practical service elements, including course layout, accessibility, green fee pricing, facility quality, and ancillary services. Purpose: This research examines how golf course characteristics influence customer satisfaction and their intention to revisit, comparing experiences across public and private courses in the Jabodetabek region. Method: A quantitative survey was conducted using purposive sampling. The study collected responses from 224 active golfers. Data were examined through Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the links among service attributes, satisfaction, and revisit intention. Findings: The analysis reveals that course layout, ease of access, green fee levels, and overall facility quality significantly shape customer satisfaction. Interestingly, green fee pricing shows a negative relationship, highlighting customers’ sensitivity to perceived value, while restaurant services were found to have no meaningful effect. In addition, customer satisfaction serves as a strong determinant of revisit intention and acts as a crucial mediator connecting service quality. Conclusions: Customer satisfaction plays a significant role in encouraging repeat visits within the golf tourism sector. Enhancing physical infrastructure, improving accessibility, and adopting customer-oriented pricing strategies are essential for sustaining loyalty. Research implication: Golf course managers should focus on layout optimization, facility upgrades, and value-based pricing models. These will enhance satisfaction and strengthen long-term customer retention in a competitive and evolving leisure market.